The impact of government expenditure on economic growth in Malaysia / Shaliza Azreen Mohd Zulkifli, Nur Amira Effendi and Nor Anis Shafai - Mohd Zulkifli, Shaliza Azreen; Effendi, Nur Amira; Shafai, Nor Anis (Universiti Teknologi MARA (UiTM), 2022)
Government spending is a major component of Gross Domestic Product (GDP). The matter of overspending comes into the perspective where it might be deemed inevitable but necessary. If the government’s budget is being overspent, it may have failed to address the real element that may boost productivity. Therefore, this research is conducted to study the impact of government expenditures on the economic growth in Malaysia using independent variables like development expenditure, education, healthcare, and gross fixed capital formation from 1980 to 2020 as guidelines. Findings of this study show development expenditure is positively significant affecting Malaysia economic growth, while education, healthcare, and gross fixed capital formation are negatively significant. A long-run relationship is also detected for the model used in this study.